Ensuring the activity of courts in the administration of justice: the USA experience - Waterfall, Scott (Public Administration and Civil Service, 2015)
The article discusses the varied responsibilities of court administrators as essential participants in the justice system. Administrators have the power to influence the judicial order and process in many ways to promote efficiency, accountability and equity.